Thomas Joseph Murray. (6th January 2023) - Twomey, Fin; Casey, James; Byrne, George; Murray, Declan
Abstract : A veterinary inspector with a history of working in animal health and food safety, Tom contributed to solving global problems. He also had a passion for travel and a curiosity for new experiences.